Feasibility Analysis of Bengkel Koding Website Using Black Box Testing and Boundary Value Analysis - Putri, Clara Edrea Evelyna Sony; Susanto, Ajib (Sinkron : jurnal dan penelitian teknik informatika, 2024)
In an era of rapid technological development, application development has become common, especially in coding. However, most websites do not give appropriate assignments and instructors to help improve coding skills. Because of this, the Bengkel Koding of Dian Nuswantoro University Semarang is a solution to improving the quality of coding learning. This research aims to identify the shortcomings in the website and ensure that the website functions as expected by the users. By testing the application like this, researchers can know which problems can affect the user experience. This research uses one of the frequently used tests, namely Black Box testing. The objective is to verify that the system's functions, inputs, and outputs align with the specified requirements. In addition to the Black Box method, this research uses a technique called Boundary Value Analysis. This technique is to identify errors or bugs that can affect the user experience by focusing on the input value boundary. The test results will use a quality ratio that will determine whether or not the system is suitable for use by users. Through 30 test cases, most website functions have been tested properly, with the feasibility level reaching 83.333%. Nonetheless, five errors or bugs were still found, emphasizing the need for further improvement. The results of this study provide valuable insights into improving the quality and convenience of users in accessing the Bengkel Koding website.